A model for forecasting future air travel demand on the North Atlantic - Taneja, Nawal K. (Cambridge, Mass. Massachusetts Institute of Technology, Flight Transportation Laboratory, [1971], 1971)
April 1970 Includes bibliographical references (p. 125-128) Introduction: One of the key problems in the analysis and planning of any transport properties and facilities is estimating the future volume of traffic that may be expected to use these properties and facilities. Estimates of this kind are now being made regularly as the transport system continues to expand. The future planning, implementation and operation of a successful transportation system requires accurate and realistic forecasts of traffic volumes. To achieve optimal policies, the planner needs to be able to predict the effect of alternate decisions. Although the planning process involves much more than a forecast of the future traffic statistics, these statistics provide the essential quantitative dimensions for the planning process. Forecasts of expected traffic are an essential prerequisite to long-range planning. The link between planning and forecasting lies in recognizing that in order to bring an expected situation under control, the planner must be provided with the entire spectrum of situations that could be anticipated and, hence, could be planned for. The reasonableness and reliability of these traffic statistics is, therefore, of vital importance to the planner. This study investigates the North Atlantic passenger travel demand. The final goal is to make a forecast of the passenger traffic on this route. It is believed that such a forecast would prove to be a critical tool for long-range planning of transport properties and facilities on both sides of the Atlantic. For this reason, it is important to be well informed about the technical and economic factors which will determine and limit the travel volume, especially for manufacturers of aircraft, domestic and international airlines, and the government. Governments, for example, must be provided with traffic forecasts if they are to provide adequate ground facilities and air traffic control systems.